Substitution between fixed, mobile, and voice over IP telephony: Evidence from the European Union - Mirjam R. J. Lange; Amela Saric (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Developments in the EU telecommunications markets require a recurrent redesign of the regulatory framework for telecommunications services. In this regard, the analysis of the substitution effects between different types of telephony is the cornerstone of market definition and therefore of effective regulation. This paper explores the access substitution between fixed-lines, mobiles, and managed VoIP in a unified EU cross-country framework. We employ a half-yearly dataset for 20 EU countries for the 2008-2011 period and apply dynamic panel data methods. Our analysis demonstrates strong access substitution between fixed-lines and mobiles and provides indicative evidence on the substitution between fixed-lines and VoIP. Overall, we find evidence in favor of access substitution and therefore of joint market definition. Regulatory obligations imposed on the market for access to fixed telephone networks might therefore be redundant.
Keywords: C23; L43; L51; L96; 330; Fixed-mobile-VoIP substitution; Telecommunications markets; (De)regulation; Market definition; Dynamic panel data analysis